2014
DOI: 10.1007/s10571-014-0129-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Arctium lappa L. Roots Against Hydrogen Peroxide-Induced Cell Injury and Potential Mechanisms in SH-SY5Y Cells

Abstract: Accumulated evidence has shown that excessive reactive oxygen species (ROS) have been implicated in neuronal cell death related with various chronic neurodegenerative disorders. This study was designed to explore neuroprotective effects of ethyl acetate extract of Arctium lappa L. roots (EAL) on hydrogen peroxide (H2O2)-induced cell injury in human SH-SY5Y neuroblastoma cells. The cell viability was significantly decreased after exposure to 200 μM H2O2, whereas pretreatment with different concentrations of EAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Previous papers reported that H 2 O 2 had cytotoxic effects in various in vitro model by a mechanism involving pro-apoptotic factors (Bax, caspases, PARP) activation and intracellular signaling pathway [ 45 51 ]. Especially, MAPK signaling pathway has been suggested as an important mechanism in oxidative stress-mediated neurodegenerative diseases [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers reported that H 2 O 2 had cytotoxic effects in various in vitro model by a mechanism involving pro-apoptotic factors (Bax, caspases, PARP) activation and intracellular signaling pathway [ 45 51 ]. Especially, MAPK signaling pathway has been suggested as an important mechanism in oxidative stress-mediated neurodegenerative diseases [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…[17] Therefore, SH-SY5Y cells are used as cellular models to explore the molecular mechanisms of oxidative stress-induced neurotoxicity. [18,19] Moreover, homogenous cerebellar granule neurons (CGNs) can be easily obtained because more than 90% of cells in cerebellum are CGNs. [20] Therefore, CGNs are widely used as a model of primary neurons to examine neuroprotective chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…ROS may attack intracellular biological macromolecules, including nuclear acids, proteins and lipids, induce dysfunction of mitochondria, and activate signaling pathways leading to apoptosis ( 6 ). Among the various ROS, H 2 O 2 easily diffuses in and out of cells and tissues ( 6 ), and is readily converted into highly reactive hydroxyl radicals by the Fenton reaction ( 7 ). Thus, H 2 O 2 has been considered to be an appropriate molecule to induce oxidative stress and is extensively used to investigate the protective effect of certain agents on cellular injury ( 8 ).…”
Section: Introductionmentioning
confidence: 99%